The European M&A Industry: A Market in the Process of Construction - Moschieri, Caterina; Campa, José Manuel (Academy of Management, 2009)
In 2007, for the first time in recent history, the volume of mergers and acquisitions by European companies surpassed that of their U.S. counterparts. This paper provides a comprehensive overview of the trends and drivers of this surge in M&A activity in the European Union. It reviews the role of the European Commission in fostering a level playing field for takeover activity and the key characteristics of M&A deals in Europe. Despite evidence of significant progress toward the development of a homogeneous market for M&As, important differences still hold among European countries both in the rules and in the patterns that M&A activity takes. The analysis suggests that this dissimilarity between Europe and the U.S. is not solely linked to the existence of a harmonized market but rather arises from unique institutional characteristics ingrained in the corporate structure of companies, which differ among European countries. This raises questions about the generalizability of current research on North American M&As to the European context.
Keywords: Markets; Industry; 53 Ciencias Económicas::5309 Organización de la industrial y política económica pública::5309.04 Estructura del mercado; ODS 9 - Industria, innovación e infraestructura